Breakthrough Therapy Designation: CDER Analysis of Requests 4 Years Into the Program. (July 2017) - Conrad, Ryan; Taylor, Kimberly; Raggio, Miranda; Harrington, Afi; Stark, Grace; Kish, Andrew; Bertha, Amy
Background: A breakthrough therapy designation is intended to facilitate and expedite development and review of new drugs to address unmet medical need in the treatment of a serious condition. Methods: The Center for Drug Evaluation and Research (CDER) at Food and Drug Administration (FDA) analyzed 364 breakthrough therapy designation requests received from program inception on July 9, 2012, through June 30, 2016. Results: Of the 364 requests received during this time, CDER granted 133 (37%), denied 182 (50%), and the sponsor withdrew 49 (13%) before CDER made a decision. Conclusion: This analysis provides information on the distinguishing characteristics of the drugs seeking this designation and the decisional factors used by CDER to either grant or deny breakthrough therapy designation requests. This paper provides greater transparency into the CDER decision process, so the public can better understand how breakthrough therapy designations are determined.